Regression of skin lesions in a patient with tuberous sclerosis complex treated with rapamycin after renal transplantation – case report and literature review - Renczyńska-Matysko, Joanna; Imko-Walczuk, Beata; Tarasewicz, Agnieszka; Dębska-Ślizień, Alicja; Rutkowski, Bolesław; Czubek, Maria (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Tuberous sclerosis complex (TSC, Bourneville-Pringle disease) is a rare disease belonging to the phakomatoses group, and is characterized by lesions affecting the skin, central nervous system, eyes and internal organs. TSC is a genetic disorder caused by mutations of the TSC1 or TSC2 gene. Products of these genes, hamartin and tuberin, create a complex that inhibits the mammalian target of rapamycin (mTOR), a key protein engaged in regulation of the cell cycle. Mutations of TSC genes lead to constitutive activation of mTOR resulting in uncontrolled proliferation, differentiation and migration of cells, the consequences of which are malformations in many organs. Crucial for diagnosis is dermatological investigation, because skin lesions can be one of the first symptoms of Bourneville-Pringle disease. Hypomelanotic macules, facial angiofibromas, forehead plaques, non traumatic periungual fibromas, shagreen patch, confetti-like skin lesions, pits in dental enamel, and gingival fibromas are the most frequent symptoms of tuberous sclerosis complex. Objective . To present regression of skin lesions in a patient with tuberous sclerosis complex treated with rapamycin as a part of immunosuppressive therapy after renal transplantation. Case report . A 49-year-old female patient with TSC recognized in 1988 was referred to the Dermatology Department in January 2010 with multiple skin lesions. She presented the following skin lesions which are characteristic for TSC: angiofibromas, shagreen patch, hypomelanotic macules, facial angiofibromas, non traumatic periungual fibromas and confetti-like skin lesions. She suffered from epileptic attacks from early infancy. In 1993 computed tomography revealed angiomyolipomas in both kidneys, which led to chronic renal failure and required bilateral nephrectomy. At the age of 44 years she underwent renal transplantation. Immunosuppressive treatment included the mTOR inhibitor – rapamycin. After 4 years of therapy with rapamycin the stabilisation of organ malformation and a significant regression of skin lesions was observed. Conclusions . Discovery of the TSC1 and TSC2 genes, the mTOR pathway and its inhibitor rapamycin is a breakthrough in tuberous sclerosis treatment. Therefore an immunosuppressive regimen with rapamycin should always be considered as the therapy of choice after kidney transplantation among patients with TSC.